Disaggregation-induced ESIPT: a novel approach towards development of sensors for hyperglycemic condition. (4th January 2019) - Sindhu, Jayant; Mayank,; Bhasin, Aman K. K.; Kaur, Navneet; Singh, Narinder; Bhasin, K. K.
Abstract : An oxazolonapthoimidazo[1, 2- a ]pyridine-based fluorescence probeONIP1 was designed and synthesized via multicomponent reaction.ONIP1 was able to distinguish human serum albumin (HSA) from and glycated-HSA via modulation of AIEE- and ESIPT-based dual channel emission properties. Abstract : Hyperglycaemia is a condition of metabolic disorder in which glycation of human serum albumin (HSA) protein occurs. Upon glycation, the α-helical region of the protein undergoes characteristic changes in its structural features. In this study, we designed a fluorescence probe that can distinguish HSA proteins from glycated HSA (GHSA) proteins. The developed probe contains an oxazolonapthoimidazo[1, 2- a ]pyridine-based moiety (ONIP1 ) and was designed using rational computational techniques. The compound exhibits aggregation-induced enhanced emission (AIEE) along with the excited-state intermolecular proton transfer (ESIPT) phenomenon. Density functional theory (DFT) calculations have provided data on ground- and excited-state energy-optimized structures and properties of the proposed enol (N*) and keto (T*) form, which is also in agreement with the solution-state experimental findings and supports the occurrence of the ESIPT phenomenon. UsingONIP1, we were able to distinguish HSA and GHSA proteins via typical modulation of AIEE and ESIPT events.